To simplify the expression \(\left(x^{-3}\cdot y^{3}\right)^{-7}\), we will apply the properties of exponents.
- Start by applying the power of a product rule, which states that \((ab)^n = a^n \cdot b^n\).
\[ \left(x^{-3} \cdot y^{3}\right)^{-7} = \left(x^{-3}\right)^{-7} \cdot \left(y^{3}\right)^{-7} \]
- Now, we can simplify each component. Using the power of a power rule, which states that \((a^m)^n = a^{m \cdot n}\):
\[ \left(x^{-3}\right)^{-7} = x^{-3 \cdot (-7)} = x^{21} \]
\[ \left(y^{3}\right)^{-7} = y^{3 \cdot (-7)} = y^{-21} \]
- Combining these results, we have:
\[ \left(x^{-3} \cdot y^{3}\right)^{-7} = x^{21} \cdot y^{-21} \]
So the equivalent expression is:
\[ x^{21} \cdot y^{-21} \]
Thus, the answer is:
Choice C: \[x^{21}\cdot y^{-21}\]